An all-inclusive digital framework for collaborative community transformation for sustainable development - Olowolayemo, Akeem; Daud, Nuha Hafizah; Tanni, Maymuna Gulfam; Omar Ba Khadher, Mohammed Abdullah (IIUM Press, 2023)
Technology as a part of the world development can be utilized for public welfare and service. In this current era people lives and activities depend mostly on technology. Consequently, technology can foster massive contribution to problem-solving in communities and can easily enable several services hitherto considered difficult. One area of interest is the utilisation of technology to enable faster solutions to common problems in a community. Monitoring the challenges and developments in a community through a community reporting and collaborative transformation system is still not that much popular despite the obvious benefits. The idea of crafting a digital collaborative transformation system becomes crucial to solving the common problems in a community and how to achieve a smooth collaborative relationship between the citizens and their respective political representatives. Consequently, this study aims to offer a comprehensive framework for the development of a digital collaborative community transformation, consisting of community members’ responses and communication linked with the person in-charge, budgeting suggestions, volunteer, as well as nomination and voting systems. The approach adopted in this study is to use exploratory strategy to discuss all the critical processes from the standpoint of the users, as well as the technology for designing, creating, and integrating the system to gather users’ inputs.Technology as a part of the world development can be utilized for public welfare and service. In this current era people lives and activities depend mostly on technology. Consequently, technology can foster massive contribution to problem-solving in communities and can easily enable several services hitherto considered difficult. One area of interest is the utilisation of technology to enable faster solutions to common problems in a community. Monitoring the challenges and developments in a community through a community reporting and collaborative transformation system is still not that much popular despite the obvious benefits. The idea of crafting a digital collaborative transformation system becomes crucial to solving the common problems in a community and how to achieve a smooth collaborative relationship between the citizens and their respective political representatives. Consequently, this study aims to offer a comprehensive framework for the development of a digital collaborative community transformation, consisting of community members’ responses and communication linked with the person in-charge, budgeting suggestions, volunteer, as well as nomination and voting systems. The approach adopted in this study is to use exploratory strategy to discuss all the critical processes from the standpoint of the users, as well as the technology for designing, creating, and integrating the system to gather users’ inputs.